Penghematan Daya pada Sistem Komunikasi Kooperatif Two-Way dengan Pengaturan Rasio Data Rate - Nasaruddin Nasaruddin; Didi Rahmadi; Rusdha Muharar (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
Currently, many communication technologies use wireless media because it can provide seamless connectivity and mobile access. In the implementation, wireless communication system faces many challenges, one of them is fading. The effect of fading on a wireless channel will also add power consumption on mobile devices and can reduce the information signal power. However, fading can be overcome by using a cooperative communication system which is a method that utilizes antenna from other users (relays) with the principle of diversity, so the performance of wireless communication system can be improved. This paper proposes power saving on two-way cooperative communication system based on data rate ratio. The method of setting the value of this data rate ratio aims to minimize power consumption in a two-way cooperative communication system, i.e., a full-duplex communication system with quantized and forward (QF) relay protocol. To obtain a minimum power consumption, the ratio of the data rate must be set on the assumption that the value of the transmit power of each source and the relay is equal. The result shows that the system performance is improved, the system SNR value becomes lower, and the power is more efficient by adjusting the ratio of data rate compared to the conventional system without power control.